Introducing and Training of the Mendeley Application as a Reference Tool in Student Scientific Articles - Simarmata, Justin Eduardo; Mone, Ferdinandus; Kehi, Yohanes Jefrianus; Naimnule, Maria (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The introducing and training of the Mendeley application for students of the Mathematics Education Study Program, Faculty of Education, University of Timor aims to improve students' understanding and skills in using Mendeley application in writing research articles. This community service activity was carried out from June 2021 to August 2021 which takes place in the Hall of the Faculty of Education, University of Timor. The method applied in this training is lecture and practice. The activity was attended by 19 students of the Mathematics Education Study Program. This service activity is very useful students because they can understand the strategy of finding quality references using the Mendeley application. This can be seen from the way of citation and references using Mendeley in the articles of those students.